A flexible model for fuel subsidy reform in Malaysia - Ismail, Shahrina; Lim, Fong Peng; Lau, Gee Choon; Yow, Kai Siong (Akademi Sains Malaysia, 2024)
Due to the current spike in crude oil prices and the economic uncertainty, the government of Malaysia is in the midst of revising the current fuel subsidy scheme that imposes caps on both petrol RON95 and diesel. Under the current scheme, all citizens are allowed to refuel subsidised petrol without any restriction. In the year 2022, the projected amount of the fuel subsidy allocation is RM28 billion, compared to RM11 billion in the previous year. To avoid an unhealthy financial position, a more structured fuel subsidy scheme is needed. We propose a framework, namely flexible fuel subsidy scheme (FLEXFUEL), that allocates the fuel subsidy to targeted consumer groups based on some predetermined ratios. Eligible citizens will be classified according to certain factors that will determine the fuel subsidy they are entitled to. The framework improves the weaknesses of the current scheme, and it is more flexible where the total allocation and the ratios are all adjustable to match the latest development of the country. More factors could also be added to the framework when necessary. We believe this is a more effective scheme that benefits both the country and citizens in the long term and simultaneously helps in reducing the environmental impacts due to fuel production and consumption.